Clinical characteristics and outcomes of inpatients with neurologic disease and COVID-19 in Brescia, Lombardy, Italy. (18th August 2020) - Benussi, Alberto; Pilotto, Andrea; Premi, Enrico; Libri, Ilenia; Giunta, Marcello; Agosti, Chiara; Alberici, Antonella; Baldelli, Enrico; Benini, Matteo; Bonacina, Sonia; Brambilla, Laura; Caratozzolo, Salvatore; et al.
Abstract : Objective: To report clinical and laboratory characteristics, treatment, and clinical outcomes of patients admitted for neurologic diseases with and without coronavirus disease 2019 (COVID-19). Methods: In this retrospective, single-center cohort study, we included all adult inpatients with confirmed COVID-19 admitted to a neuro-COVID unit beginning February 21, 2020, who had been discharged or died by April 5, 2020. Demographic, clinical, treatment, and laboratory data were extracted from medical records and compared (false discovery rate corrected) to those of neurologic patients without COVID-19 admitted in the same period. Results: One hundred seventy-three patients were included in this study, of whom 56 were positive and 117 were negative for COVID-19. Patients with COVID-19 were older (77.0 years, interquartile range [IQR] 67.0–83.8 years vs 70.1 years, IQR 52.9–78.6 years, p = 0.006), had a different distribution regarding admission diagnoses, including cerebrovascular disorders (n = 43, 76.8% vs n = 68, 58.1%), and had a higher quick Sequential Organ Failure Assessment (qSOFA) score on admission (0.9, IQR 0.7–1.1 vs 0.5, IQR 0.4–0.6, p = 0.006). In-hospital mortality rates (n = 21, 37.5% vs n = 5, 4.3%, p < 0.001) and incident delirium (n = 15, 26.8% vs n = 9, 7.7%, p = 0.003) were significantly higher in the COVID-19 group. Patients with COVID-19 and without COVID with stroke had similar baseline characteristics, but patients with COVID-19 had higher modified Rankin Scale scores at discharge (5.0, IQR 2.0–6.0 vs 2.0, IQR 1.0–3.0, p < 0.001), with a significantly lower number of patients with a good outcome (n = 11, 25.6% vs n = 48, 70.6%, p < 0.001). In patients with COVID-19, multivariable regressions showed increasing odds of in-hospital death associated with higher qSOFA scores (odds ratio [OR] 4.47, 95% confidence interval [CI] 1.21–16.5, p = 0.025), lower platelet count (OR 0.98, 95% CI 0.97–0.99, p = 0.005), and higher lactate dehydrogenase (OR 1.01, 95% CI 1.00–1.03, p = 0.009) on admission. Conclusions: Patients with COVID-19 admitted with neurologic disease, including stroke, have a significantly higher in-hospital mortality and incident delirium and higher disability than patients without COVID-19.